Prion-like propagation of post-translationally modified tau in alzheimer's disease: a hypothesis - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
The microtubule-associated protein Tau plays a key role in the neuropathology of Alzheimer's disease by forming intracellular neurofibrillary tangles. Tau in the normal physiological condition helps stabilize microtubules and transport. Tau aggregates due to various gene mutations, intracellular insults and abnormal post-translational modifications, phosphorylation being the most important one. Other modifications which alter the function of Tau protein are glycation, nitration, acetylation, methylation, oxidation, etc. In addition to forming intracellular aggregates, Tau pathology might spread in a prion-like manner as revealed by several in vitro and in vivo studies. The possible mechanism of Tau spread can be via bulk endocytosis of misfolded Tau species. The recent studies elucidating this mechanism have mainly focussed on the aggregation and spread of repeat domain of Tau in the cell culture models. Further studies are needed to elucidate the prion-like propagation property of full-length Tau and its aggregates in a more intense manner in vitro as well as in vivo conditions. Varied post-translational modifications can have discrete effects on aggregation propensity of Tau as well as its propagation. Here, we review the prion-like properties of Tau and hypothesize the role of glycation in prion-like properties of Tau. This post-translationally modified Tau might have an enhanced propagation property due to differential properties conferred by the modifications.
Keywords: Alzheimer disease; Post-translational modifications of tau; Propagation of tau; Tau; Tauopathies

Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Protein-capped metal nanoparticles inhibit tau aggregation in alzheimer's disease - Sonawane, Shweta Kishor; Ahmad, Absar; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The Alzheimer's disease (AD) therapeutic research is yielding a large number of potent molecules. The nanoparticle-based therapeutics against the protein aggregation in AD is also taking a lead especially with amyloid-beta as a primary target. In this work, we have screened for the first time protein-capped (PC) metal nanoparticles for their potency in inhibiting Tau aggregation in vitro. We present a novel function of PC-Fe3O4 and PC-CdS nanoparticles as potent Tau aggregation inhibitors by fluorescence spectrometry, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and electron microscopy. We demonstrate that the biologically synthesized PC-metal nanoparticles, especially iron oxide do not affect the viability of neuroblastoma cells. Moreover, PC-CdS nanoparticles show dual properties of inhibition and disaggregation of Tau. Thus, the nanoparticles can take a lead as potent Tau aggregation inhibitors and can be modified for specific drug delivery due to their very small size. The current work presents unprecedented strategy to design anti-Tau aggregation drugs, which provides interesting insights to understand the role of biological nanostructures in Alzheimer's disease.

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

P301 L, an FTDP-17 mutant, exhibits enhanced glycation in vitro - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2020)
Background: Frontotemporal dementia and parkinsonism-linked to chromosome-17 are a group of diseases with tau mutations leading to primary tauopathies which include progressive supranuclear palsy, corticobas al syndrome, and frontotemporal lobar degeneration. Alzheimer's disease is a non-primary tauopathy, which displays tau neuropathology of excess tangle formation and accumulation. FTDP-17 mutations are responsible for early onset of AD, which can be attributed to compromised physiological functions due to the mutations. Tau is a microtubule-binding protein that secures the integrity of polymerized microtubules in neuronal cells. It malfunctions owing to various insults and stress conditions-like mutations and post-translational modifications. Objective: In this study, we modified the wild type and tau mutants by methyl glyoxal and thus studied whether glycation can enhance the aggregation of predisposed mutant tau. Methods: Tau glycation was studied by fluorescence assays, SDS-PAGE analysis, conformational evaluation, and transmission electron microscopy. Results: Our study suggests that FTDP-17 mutant P301 L leads to enhanced glycation-induced aggregation as well as advanced glycation end products formation. Glycation forms amorphous aggregates of tau and its mutants without altering its native conformation. Conclusion: The metabolic anomalies and genetic predisposition have found to accelerate tau-mediated neurodegeneration and prove detrimental for the early-onset of Alzheimer's disease.
Keywords: advanced glycation end products; Alzheimer's disease; FTDP-17; tau glycation

Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

Baicalein inhibits heparin-induced Tau aggregation by initializing non-toxic Tau oligomer formation - Sonawane, Shweta Kishor; Uversky, Vladimir N.; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Amyloid aggregate deposition is the key feature of Alzheimer's disease. The proteinaceous aggregates found in the afflicted brain are the intra-neuronal neurofibrillary tangles formed by the microtubule-associated protein Tau and extracellular deposits, senile plaques, of amyloid beta (A beta) peptide proteolytically derived from the amyloid precursor protein. Accumulation of these aggregates has manifestations in the later stages of the disease, such as memory loss and cognitive inabilities originating from the neuronal dysfunction, neurodegeneration, and brain atrophy. Treatment of this disease at the late stages is difficult, and many clinical trials have failed. Hence, the goal is to find means capable of preventing the aggregation of these intrinsically disordered proteins by inhibiting the early stages of their pathological transformations. Polyphenols are known to be neuroprotective agents with the noticeable potential against many neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Prion diseases. Methods: We analyzed the capability of Baicalein to inhibit aggregation of human Tau protein by a multifactorial analysis that included several biophysical and biochemical techniques. Results: The potency of Baicalein, a polyphenol from the Scutellaria baicalensis Georgi, against in vitro Tau aggregation and PHF dissolution has been screened and validated. ThS fluorescence assay revealed the potent inhibitory activity of Baicalein, whereas ANS revealed its mechanism of Tau inhibition viz. by oligomer capture and dissociation. In addition, Baicalein dissolved the preformed mature fibrils of Tau thereby possessing a dual target action. Tau oligomers formed by Baicalein were non-toxic to neuronal cells, highlighting its role as a potent molecule to be screened against AD. Conclusion: In conclusion, Baicalein inhibits aggregation of hTau40 by enhancing the formation of SDS-stable oligomers and preventing fibril formation. Baicalein-induced oligomers do not affect the viability of the neuroblastoma cells. Therefore, Baicalein can be considered as a lead molecule against Tau pathology in AD.
Keywords: Alzheimer's disease; Baicalein; Tau dissolution; Tau inhibition; Tau Oligomers

Epigallocatechin-3-gallate modulates tau post-translational modifications and cytoskeletal network - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Oncotarget, 2021)
BACKGROUND: Alzheimer's disease is a type of dementia denoted by progressive neuronal death due to the accumulation of proteinaceous aggregates of Tau. Post-translational modifications like hyperphosphorylation, truncation, glycation, etc. play a pivotal role in Tau pathogenesis. Glycation of Tau aids in paired helical filament formation and abates its microtubule-binding function. The chemical modulators of Tau PTMs, such as kinase inhibitors and antibody-based therapeutics, have been developed, but natural compounds, as modulators of Tau PTMs are not much explored. MATERIALS AND METHODS: We applied biophysical and biochemical techniques like fluorescence kinetics, oligomerization analysis and transmission electron microscopy to investigate the impact of EGCG on Tau glycation in vitro. The effect of glycation on cytoskeleton instability and its EGCG-mediated rescue were studied by immunofluorescence microscopy in neuroblastoma cells. RESULTS: EGCG inhibited methyl glyoxal (MG)-induced Tau glycation in vitro. EGCG potently inhibited MG-induced advanced glycation endproducts formation in neuroblastoma cells as well modulated the localization of AT100 phosphorylated Tau in the cells. In addition to preventing the glycation, EGCG enhanced actin-rich neuritic extensions and rescued actin and tubulin cytoskeleton severely disrupted by MG. EGCG maintained the integrity of the Microtubule Organizing Center (MTOC) stabilized microtubules by Microtubule-associated protein RP/EB family member 1 (EB1). CONCLUSIONS: We report EGCG, a green tea polyphenol, as a modulator of in vitro methylglyoxal-induced Tau glycation and its impact on reducing advanced glycation end products in neuroblastoma cells. We unravel unprecedented function of EGCG in remodeling neuronal cytoskeletal integrity.
Keywords: Alzheimer’s disease; tau glycation; Tau glycation inhibition; tau protein; Tau PTMs

Extracellular HDAC6 ZnF UBP domain modulates the actin network and post-translational modifications of Tau - Balmik, Abhishek Ankur; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Microtubule-associated protein Tau undergoes aggregation in Alzheimer`s disease (AD) and a group of other related diseases collectively known as Tauopathies. In AD, Tau forms aggregates, which are deposited intracellularly as neurofibrillary tangles. Histone deacetylase-6 (HDAC6) plays an important role in aggresome formation, where it recruits polyubiquitinated aggregates to the motor protein dynein. Methods: Here, we have studied the effects of HDAC6 ZnF UBP on Tau phosphorylation, ApoE localization, GSK-3 beta regulation and cytoskeletal organization in neuronal cells by immunocytochemical analysis. This analysis reveals that the cell exposure to the UBP-type zinc finger domain of HDAC6 (HDAC6 ZnF UBP) can modulate Tau phosphorylation and actin cytoskeleton organization. Results: HDAC6 ZnF UBP treatment to cells did not affect their viability and resulted in enhanced neurite extension and formation of structures similar to podosomes, lamellipodia and podonuts suggesting the role of this domain in actin re-organization. Also, HDAC6 ZnF UBP treatment caused increase in nuclear localization of ApoE and tubulin localization in microtubule organizing centre (MTOC). Therefore, our studies suggest the regulatory role of this domain in different aspects of neurodegenerative diseases. Upon HDAC6 ZnF UBP treatment, inactive phosphorylated form of GSK-3 beta increases without any change in total GSK-3 beta level. Conclusions: HDAC6 ZnF UBP was found to be involved in cytoskeletal re-organization by modulating actin dynamics and tubulin localization. Overall, our study suggests that ZnF domain of HDAC6 performs various regulatory functions apart from its classical function in aggresome formation in protein misfolding diseases.
Keywords: Actin; Cytoskeleton; HDAC6; Microtubule; neurodegeneration; Phosphorylation; Podonut; Podosomes; Tau; Tauopathies

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation

Dual modification of tau by pseudophosphorylation and glycation does not enhance amorphous aggregation - Chinnathambi, Subashchandrabose; Sonawane, Shweta Kishor; Chandrashekar, Madhura; Chidambaram, Hariharakrishnan; Thulasiram, Shrivatsa; Kulkarni, Mahesh J. (Cellular Physiology and Biochemistry, 2024)
<h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Background/Aims: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The neurofibrillary tangles consisting of Tau protein are an important pathology in Alzheimer’s disease. The paired helical filaments of Tau form most of the NFTs. These PHFs of Tau are found to carry numerous post-translational modifications, which stabilize them and aid in aggregation. The mechanistic function of Tau is to bind and stabilize the axonal microtubules. Hyperphosphorylation of Tau causes it to compromise its physiological function and accumulate in the neurons in the form of aggregates. Such residue-specific phosphorylation has been studied by employing Tau pseudophosphorylation mutants. But in addition to phosphorylation, several other modifications also aid in stabilizing the Tau PHF. Glycation is one such non-enzymatic PTM caused by sugars and their reactive intermediates. In this study, we employed the pseudophosphorylated Tau double mutants (262/404D, 262/396D, and 231/262) for studying their modification by methyl glyoxal, a reactive intermediate of glucose metabolism.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Methods: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> We studied various biophysical properties like aggregation propensity, Advanced glycation end-product formation, and global conformation of the Tau with dual modifications. Our study includes the use of <i style="box-sizing: border-box; color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">in vitro <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">techniques e.g., ThS fluorescence assay, electron microscopy, CD spectroscopy, SDS-PAGE.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Results: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The overall result of the study suggest that the MG-induced Tau aggregation is influenced by the residue-specific Tau phosphorylation.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Conclusion: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> In conclusion, the combinatorial effect of discreet PTMs on Tau function could lead to a better understanding of Tauopathy.